Development of electrode tooling in electrical discharge machining - Goh, Khoon Kwee (2014)
In recent years, the demand to produce micro component had increased hugely as the micro component can provide several advantages. Among the advantages would be miniaturized product can be achieve, better performance and special properties which add values to the product. Microgrooves, micro slit and some other micro geometry which often encounter on the surface of the component would directly affect its performance. This simply means the approaches to fabricate and the finishing of such features is significantly important towards the performance of the component. As the demand on the size of the component produced is favoring towards miniature, Micro EDM was introduced. In this present study, it is proposed that a rotating disk electrode is to mount on a fixture in such a way that multiple orientations machining can be achieved. The fixture also ensures the machining characteristic of the rotating disk electrode is preserved. On the other hand, another off-centered rotating electrode tool is developed to fabricate circular grooves on a planar workpiece. This function is currently cannot be achieved by using the conventional rotating pin electrode on the machine using for this project. Machining is carried out using the designed tools on a workpiece and surface finish is analyzed. Both approach demonstrated as a promising way to achieved desired micro groove and slit with much efficiency. Some good finishing micro slit and groove can be obtained through the proposed approaches.